COMPARITIVE EVALUATION OF THREE NOVEL MOUTHWASHES ON SALIVARY BUFFERING CAPACITY IN SCHOOL CHILDREN: AN INVIVO STUDY - P. PRATHYUSHA; SWATHI.B; BOLISETTY ATULITHA; K. SREE LAKSHMI; K. NAVEEN KRISHNA; P.K. SARASWATHI BAI (The Bioscan, 2026)
Background : Saliva’s buffering capacity is the key factor in maintaining oral homeostasis.Despite fluoride mouthwash being the gold standard,its harmful effects have led to the development of newer formulations containing nanosilver, hyaluronic acid as they have superior antibacterial,remineralizing effects.Hence,the present study is aimed to compared the effects of these mouthwashes on buffering capacity of saliva. Methods : This study included 66 healthy children aged 7 to 12 years .Salivary samples were collected from the participants,baseline salivary buffering capacity was measured using pH meter.Participants were divided into 3 equal groups as Group1 received fluoride mouthwash,Group 2 received hyaluronic mouth wash,Group 3 received nanosilver mouthwash.All the participants were allowed to rinse mouthwashes for about 45 secs.Salivary samples were obtained again after 30 min for measuring the post intervention buffering capacity, and the same procedure was repeated for the period of 15 days. Results : After 15 days,On intra group comparison,both fluoride and hyaluronic acid mouthwash groups showed a statistically significant increase in salivary buffering capacity (p < 0.001),whereas nanosilver group showed a non-significant change (p > 0.05).Intergroup comparison revealed a highly significant difference among all groups (p < 0.001), with hyaluronic acid mouthwash demonstrating greatest improvement, followed by nanosilver and fluoride.Post hoc analysis confirmed significant differences between all pairwise comparisons. Conclusion : Hyaluronic acid mouthwash demonstrated superior effectiveness in improving buffering capacity compared to fluoride and nanosilver mouthwashes.It serves as a promising alternative for enhancing oral health in children.